Selection and control of applications in pervasive displays - Taivan, Constantin (2012)
Public displays are progressively embedded in urban settings. Such displays become elements of an integrated pervasive ecosystem in which vari-ous displays with multiple applications are accessed by multiple viewers. Still, many public displays employ content that is based on pre-defined schedules as encountered in conventional digital signage systems. We envision future dis-play deployments embedding many applications that are running concurrently and able to continuously react to users’ requests. In this paper, we investigate application selection and control concepts based on a mixed-initiative scenario in which display system and viewers are both involved in the process of content presentation. Our approach is inspired by traditional GUI interaction concepts and design considerations of sensing systems. Hence, this research would in-form the design of novel techniques for application selection and control in per-vasive display environments.